Short Mindfulness-Based Relaxation Training Has No Effects on Executive Functions but May Reduce Baseline Cortisol Levels of Boys in First Grade: A Pilot Study - Adam Koncz; Reka Kassai; Zsolt Demetrovics; Zsofia K. Takacs (MDPI AG, 2022)
(1) Background: Executive functions are important for academic performance and school readiness. Children's executive function skills are found to be improved by mindfulness-based interventions, and these programs are also effective in stress reduction. The aim of this study was to evaluate the feasibility and the effects of a short mindfulness-based relaxation training compared to a passive control condition right before school entry on executive function skills and cortisol levels. (2) Methods: The feasibility and the effects of the intervention before school entry were tested with 61 preschoolers. The final sample consisted of 51 participants (Mage = 81.90 months, SD = 5.45; 41% male). Short-term memory, executive function skills and cortisol levels before and after the intervention were assessed. Additionally, cortisol levels were assessed one week and one month after school entry. (3) Results: There was a significant sex difference in the effects of the intervention on children's cortisol levels (p = 0.026, η2 = 0.134). The mindfulness-based relaxation training applied before school entry prevented a rise in boys' cortisol levels one week after starting school. (4) Conclusion: A short mindfulness-based intervention before starting school could be effective in fostering physiological stress management in boys.